Tatsiramos, Assortative mating and education gradients within and across generations - Paul Bingley; Lorenzo Cappellari; Konstantinos Tatsiramos (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2026)
We develop a model that links education-outcome gradients to intergenerational transmission, distinguishing joint from parent-specific channels under assortative mating. Using Danish administrative data on family quartets, we estimate the own education-outcome gradient and, in addition, intergenerational gradients in long-run earnings, disposable income, assets, and wealth. Gradients differ sharply across domains: for earnings and income, joint transmission matters alongside individual-specific heterogeneity; for assets and especially wealth, gradients are dominated by parent-specific channels. Exploiting Danish schooling reforms, we show that the composition of financial gradients varies with access to schooling.
Keywords: J62; D31; J12; I24; E21; J24; 330; Assortative mating; Education gradients; Intergenerational mobility